A Review: Role of Inulin in Animal Nutrition - Birmani, Muhammad Waseem; Nawab, Aamir; Ghani, Muhammad Waseem; Li, Guanghui; Xiao, Mei; An, Lilong (Journal of Food Technology Research, 2019)
Inulin is an oligosaccharide which can be used in the animal diet as a functional fiber. Among other natural plant-derived fructans, inulin has so many beneficial effects on the immune system, lipid metabolism, and helps in mineral absorption and has the ability to balance the intestinal microbiota of animals. Increasing global meat demand and ban of antibiotics as growth promoters in animal feed due to its residual effects in human food are the factors driving the growth of inulin as a feed additive. As feed additive in animal feed inulin has a positive effect on intestinal health and have the potential to improve the immunity of livestock and poultry. From few years, inulin has been making headlines in animal nutrition, but it remains a little-known feed ingredient and is even less used in the feed industry. Therefore, the objective of this review is to provide recently applied knowledge to the researchers about the general beneficial functions of inulin in the animal body and its application in the animal feed industry.